Dionysus en Limnais - Pickard, John (Gorgias Press, 2009)
This paper discusses the literary and physical evidence for the Lenaeum (the sacred precinct of Dionysios in Athens), a site whose location was lost
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: HISTORY / Ancient / Greece